Computational fluid dynamics vs. inverse dynamics methods to determine passive drag in two breaststroke glide positions - Costa, L.; Mantha, V. R.; Silva, A. J.; Fernandes, R. J.; Marinho, D. A.; Vilas-Boas, J. P.; Machado, L.; Rouboa, A. (Journal of Biomechanics, 2015)
Computational fluid dynamics (CFD) plays an important role to quantify, understand and "observe" the water movements around the human body and its effects on drag (D). We aimed to investigate the flow effects around the swimmer and to compare the drag and drag coefficient (CD) values obtained from experiments (using cable velocimetry in a swimming pool) with those of CFD simulations for the two ventral gliding positions assumed during the breaststroke underwater cycle (with shoulders flexed and upper limbs extended above the head-GP1; with shoulders in neutral position and upper limbs extended along the trunk-GP2). Six well-trained breaststroke male swimmers (with reasonable homogeneity of body characteristics) participated in the experimental tests; afterwards a 3D swimmer model was created to fit within the limits of the sample body size profile. The standard k-e turbulent model was used to simulate the fluid flow around the swimmer model. Velocity ranged from 1.30 to 1.70 m/s for GP1 and 1.10 to 1.50 m/s for GP2. Values found for GP1 and GP2 were lower for CFD than experimental ones. Nevertheless, both CFD and experimental drag/drag coefficient values displayed a tendency to jointly increase/decrease with velocity, except for GP2 CD where CFD and experimental values display opposite tendencies. Results suggest that CFD values obtained by single model approaches should be considered with caution due to small body shape and dimension differences to real swimmers. For better accuracy of CFD studies, realistic individual 3D models of swimmers are required, and specific kinematics respected. siehe auch: https://www.researchgate.net/publication/273321229_Computational_Fluid_Dynamics_vs_Inverse_Dynamics_methods_to_determine_passive_drag_in_two_breaststroke_glide_positions